PENGEMBANGAN SISTEM INFORMASI MONITORING KINERJA KEGIATAN PEMERINTAHAN MENGGUNAKAN FRAMEWORK SCRUM - _, Muhaemin (IST AKPRIND YOGYAKARTA, 2017)
A common problem faced by the planning (various Ministries / Agencies) is the difficulty of measuring the performance of activities and budget absorption capacity for the benefit of governance, especially in the two years back, where frequent cuts by the Ministry of Finance. Performance Monitoring Information Systems and Finance Program helps to process of planning and monitoring the implementation of activities that improve the ease of doing evaluation and reporting of producing quality data quickly and accurately. Application development of monitoring and evaluation activities in the planning department is using SCRUM which is part of the methodology AGILE which has a flexible nature can be applied to system development is quite dynamic changes are a result of requests from users who are not defined as to what form of reporting for process monitoring and evaluation activities at the planning Director General of Bina Bangda - Kemendagri.